(untitled) (Journal of the College of Basic Education, 2024)
To identify the level of expressive performance and the level of productive thinking among the students of the fifth scientific grade. A female student was selected using the simple random stratified method from the research community, which consisted of (10,200) male and female students from the fifth scientific grade students in the daytime preparatory schools in the center of Diyala Governorate. As the reliability coefficient reached (0.97), and the agreement with another corrector reached (0.89( A test for productive thinking was built, consisting of (24) items, including (20) objective items for critical thinking and (4) essay items for creative thinking. 0.93), and using the correction equation with Another corrector (0, 82) As for the validity of the test, it was verified by virtual validity and factorial analysis, and the researcher used the following statistical methods (Pearson’s correlation coefficient, and Cronbach’s alpha equation( The results showed that the students of the fifth scientific grade have the ability to expressive performance, and are distinguished by their possession of productive thinking skills, and the existence of a correlation between expressive performance and productive thinking skills. Making students the educational process and giving them sufficient freedom to express their opinions without hesitation or fear, and this brings students to the level of good expressive performance. In light of this, the researcher suggested several proposals, including:More studies and research to identify the relationship between other language branches and skills, such as identifying the relationship between expressive performance, rhetorical skills, and literary skills. The unfortunate owner gave her away